SPTAN1-associated developmental and epileptic encephalopathy - T. V. Kozhanova; S. S. Zhilina; T. I. Meshcheryakova; E. G. Lukyanova; E. S. Bolshakova; S. O. Ayvazyan; K. V. Osipova; P. A. Vlasov; A. I. Krapivkin; N. N. Zavadenko (Эпилепсия и пароксизмальные состояния)
The article presents the clinical cases of 6 patients with epilepsy, psychomotor and speech developmental delay. The heterozygous variants of the nucleotide sequence in SPTAN1 gene were detected by whole exome sequencing. Mutations in SPTAN1 gene have been described in patients with developmental and epileptic encephalopathy 5 (ОMIM: 613477). The clinical history, electroencephalographic and magnetic resonance imaging data of our patients are similar in children with variants in SPTAN1 gene described previously. It was shown that variants in SPTAN1 gene located closer to the C-terminal region are associated with a more severe phenotype, whereas the variants near the N-region – with a milder course of the disease without structural brain anomalies. However, further research is necessary in the future to better understand genotype-phenotypic correlations in SPTAN1-associated encephalopathy.